EUROPEAN TERATOLOGY INFORMATION SERVICE: EXPERIENCE, PROBLEMS AND PERSPECTIVES - A.V. Ostrovskaya; K. Schefer; L. von Stackelberg (Union of pediatricians of Russia, 2007)
Congenital malformations are still the important medical and social issue. They take the second place among the reasons for the infant mortality and cause up to 18,3% of disablement cases among the children. Exogenous factors, effecting the growing fetus, are very essential along with the genetic matters among the reasons for the congenital malformations. The importance of information on the teratogenic potential of the medications is acknowledged by the doctors from various countries. The article outlines the information on entis activity - European network of teratology information services - a non profit organization, rendering consulting services to the pregnant women and medical staff, regarding the embryo and fetotoxic actions of the medications. The authors highlight the history of entis, its objectives, principles of operation and consulting algorithm and list the basic scientific publications by the entis members for the recent years. The article deals with the most obvious problems, which the organization members face, first of all - the quality of the information they receive. The authors also provide the substantiation for the necessity to develop such an information service in Russia and express hope for the successful development of the entis subsidiary they formed in Moscow.Key words: congenital malformations, medications, pregnancy, embryotoxicity.